Serum prolidase, malondialdehyde and catalase levels for the evaluation of oxidative stress in patients with peripheral vertigo. - Ozbay, Isa; Topuz, Muhammet Fatih; Oghan, Fatih; Kocak, Havva; Kucur, Cuneyt (My University, 2021)
We aimed to evaluate oxidative stress in patients with peripheral vertigo by measuring serum prolidase, malondialdehyde (MDA) and catalase levels.

A total of 30 patients (age: 60 <) with peripheral vertigo and 30 healthy subjects were recruited. Blood samples were collected from both groups and serum prolidase levels were measured using enzyme-linked immunosorbent assay (ELISA). MDA and catalase levels were measured by the spectrophotometric method.

The most common cause of vertigo was BPPV (53.3%), followed by Ménière's disease (16.6%), vestibular neuritis (13.3%), lateral semicircular canal fistula (3.3%), and idiopathic vertigo (13.3%). Mean serum prolidase activity and MDA levels were significantly higher in the vertigo patients than in the control subjects (P < 0.05); however, there was no statistically significant difference in mean serum catalase levels between the groups (P > 0.05).

We concluded that serum prolidase and MDA levels may be used as markers of oxidative stress in patients with peripheral vertigo.
Keywords: Catalase; Malondialdehyde; Oxidative stress; Peripheral vertigo; Prolidase